2021
DOI: 10.25115/eea.v39i5.4829
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Brand Management in the Market

Abstract: The modern market is characterized by ups and downs associated with both external negative influences and expectations, and with the structural restructuring of the market. The result of these transformations was the transformation of the methodological and practical foundations of the formation, functioning and development of marketing and advertising activities, the leading role among which is the development and management of the company's brand.The development and management of a brand, or the branding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…promotional activities) but also through long-term ones aimed at enhancing the value of their brands. To obtain high levels of brand equity, the brewing firms need to realize a careful process of brand management to ensure that the brand image perceived by their consumers coincides as much as possible with that desired at the company level (Mazaraki et al, 2021). Notably, this process could be implemented by exploiting those variables investigated within this study that showed a significant and positive impact on brand equity.…”
Section: Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…promotional activities) but also through long-term ones aimed at enhancing the value of their brands. To obtain high levels of brand equity, the brewing firms need to realize a careful process of brand management to ensure that the brand image perceived by their consumers coincides as much as possible with that desired at the company level (Mazaraki et al, 2021). Notably, this process could be implemented by exploiting those variables investigated within this study that showed a significant and positive impact on brand equity.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…From this perspective, brand equity represents the “differential effect that knowing the brand name has on customer response to the product and its marketing” (Kotler and Armstrong, 2010, p. 260). Therefore, a careful process of brand management becomes crucial for firms since it allows to make sure that the brand image perceived by consumers coincides as much as possible with that desired at the company level (Mazaraki et al. , 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The researchers from the UAE (Arnaut et al, 2023) study shadowing in terms of its impact on the energy market, because the shadow economy covers all types of activities outside the formal economy. Activities in the shadow economy are mostly hidden from tax officials and regulators, and the existence of the shadow economy is likely to influence energy conservation and carbon reduction policies (Mazaraki et al, 2021;Tiutiunyk et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sources: Sobotkiewicz, 2020;Caramidaru & Ionica, 2021;Mazaraki et al, 2021;Recabarren-Domínguez et al, 2022 Command and control approach. Its use is rather limited since it is used for simple one-time actions performed by one person as a rule.…”
Section: Figure 1 Approaches To Managing An Organizationmentioning
confidence: 99%